Measurements of stable ruthenium fission products in nuclear reactor fuel samples - Genna M. Patton; Zachary A. Torrano; Amanda Salazar; Jeffrey Miller; Matthew E. Sanborn; Susan K. Hanson (Scientific Reports)
Abstract Ruthenium isotopes produced by fission in nuclear materials could be valuable signatures for nuclear verification or non-proliferation monitoring. In this study, ruthenium (Ru), uranium (U), and plutonium (Pu) isotope ratios and concentrations were measured in six different samples taken along a single nuclear fuel rod from a pressurized water reactor (PWR). The Ru isotope ratios $$^{100}$$ Ru/ $$^{101}$$ Ru, $$^{102}$$ Ru/ $$^{101}$$ and $$^{104}$$ Ru/ $$^{101}$$ Ru increase upon moving from the end of the rod towards the center, correlating with the amount of burnup of the fuel indicated by U and Pu isotope ratios. Ruthenium fission product concentrations also increase near the center of the rod, consistent with other isotopic and elemental concentration data indicative of burnup. The measured Ru ratios clearly comprise inputs from both fission and neutron capture reactions. These measurements serve as important experimental validation of previous theoretical studies suggesting that Ru isotope ratios reflect the burnup of nuclear fuel and could be used to distinguish between reactor types.